A Current Sensing Biosensor for BOD Rapid Measurement. (26th October 2020) - Liu, Yiman; Li, Jie; Wan, Nianxin; Fu, Tianyu; Wang, Lili; Li, Cong; Qie, Zhonghui; Zhu, Ao
Abstract : In order to improve the practicality of the rapid biochemical oxygen demand (BOD) method, a highly sensitive rapid detection method for BOD that is based on establishing the correlation between current and dissolved oxygen (DO) was developed. In this experiment, Bacillus subtilis was used as the test microorganism, and the embedding method was used to achieve quantitative fixation of microorganisms, which could increase the content of microorganisms and prolong the service life of the biological element. The conductivity (COND) probe is used as a sensing element, so that the testing value can be read every second. In the program, the moving average method is used to process the collected data so that the value can be read every minute. National standard samples were detected to test the accuracy and stability of the method. The results showed that relative error and analytical standard deviations were less than 5%. Different polluted water was tested to evaluate its application range. The results showed that relative error was less than 5%. The results of the method are consistent with the results of the wastewater sample obtained by the BOD5 standard method. The proposed rapid BOD current sensing biosensor method should be promising in practical application of wastewater monitoring.